Kepercayaan Followers Terhadap Influencer Dinda Azzura (@Dinzzur) dalam Mereview Produk Kecantikan Melalui Media Sosial Instagram - Rahmatul Ulya; Cut Lusi Chairun Nisak; Elita Aidillah; Mutmainnah Mutmainnah (PT Riset Mandiri Nusantara, 2025)
Abstract. Dinda Azzura (@dinzzur) is a beauty influencer who has built her followers’ trust through content shared on the social media platform Instagram. She consistently provides honest beauty product reviews, making her a reference point for followers in understanding products that suit their skin needs and in making purchasing decisions. This study aims to explore how followers’ trust is formed through beauty product reviews conducted by Dinda Azzura. This research employs a qualitative method with a mixed netnographic approach and adopts the theoretical framework of symbolic interactionism. Data were collected through observation, interviews, and documentation, including photos, feed videos, short videos (reels), comments, and content from the broadcast channel of the Instagram account @dinzzur. The findings show that followers’ trust in Dinda is built through open and honest interaction. Dinda’s authenticity in delivering transparent and educational reviews strengthens her credibility as an influencer. She also maintains consistent communication through visually engaging content and direct responses to her followers’ questions or comments. However, the study also reveals a tendency toward bias, where followers often trust Dinda’s product recommendations without conducting further research. Despite her efforts to provide educational content, many followers remain uncritical in evaluating the information they receive. Thus, this study highlights how social media platforms such as Instagram can shape bias in purchasing decisions, particularly when a high level of trust in an influencer leads followers to overlook critical personal evaluation processes. Keywords: Influencer, Instagram, Netnography, Symbolic Interactionism, Trust